Baby's first words - Sirett, Dawn (New York DK Publishing, 2018)
The cool, high-contrast design of this book will appeal to parents and children alike. Packed with babies' first words, from socks and shoes, to apples and trucks, but packaged with style, this book is just right for design-conscious adults and their information-hungry babies
Linguistic notions
Keywords: Linguistic notions